Confidence Management: On Interpersonal Comparisons in Teams - Benoît S.Y. Crutzen; Otto H. Swank; Bauke Visser (Tinbergen Institute, 2007)
Organization differ in the degree to which they differentiate employees by ability. We analyse how the effect of differentiation on employee morale may explain this variation. By comparing employees using ordinary talk, a manager boosts the self-image of some, but hurts that of others. Whether the net effect is positive for the organization depends on the degree of synergy between employees and on the shape of their objective function. An implication for relative performance pay is that it yields a double dividend or constitutes a double-edged sword.
Keywords: D82; L23; J31; 330; Comparisons; Confidence; Teams; Cheap talk; Lohnstruktur; Leistungsmotivation; Asymmetrische Information; Verhalten in Organisationen